The influence of fire and grazing on tallgrass prairie streams and herpetofauna - Larson, Danelle Marie (Kansas State University, 2014)
Tallgrass prairie evolved with fire-grazer interactions. Fire and grazing are vital processes for maintaining grasslands and cattle production, and therefore will be continued as land management schemes. The effects of fire and grazers on prairie streams are understudied, but may significantly influence stream ecology. This dissertation examined how prescribed burning, bison grazing, and patch-burn grazing (by cattle) influence water quality, stream biota, and riparian amphibians and reptiles at Konza Prairie, Kansas, or Osage Prairie, Missouri. Using Global Positioning System, we monitored bison and cattle distribution throughout watersheds. The immediate effects of prescribed burning were examined at both Konza and Osage Prairies. The impacts of bison on water quality were determined by using a long-term dataset from Konza Prairie and compared watersheds with and without bison. Amphibian and reptile assemblages were monitored for two years at Osage, and assemblage data were analyzed using redundancy analysis, permuted analysis of variance, and occupancy modeling. A patch-burn grazing experiment occurred for 5 years at Osage (2 years pretreatment data and 3 years of treatments) and was analyzed using a before-after, control-impact design. Prescribed burning had minimal effects on water chemistry. At Konza Prairie, bison did not alter water quality likely because they spent negligible time (<5%) in streams. Contrarily, cattle at Osage Prairie significantly increased stream concentrations of total suspended solids, nutrients, Escherichia coli bacteria, algal biomass, and primary production. Unlike bison, cattle spent significant time (~21%) in streams if allowed access to riparian zones. In watersheds with cattle excluded from streams by riparian fencing, water quality contaminant concentrations increased significantly, but not to the magnitude of unfenced streams. Amphibian abundance and richness were not different among patch types; instead, they were restricted to specific basins. However, reptiles displayed preference for certain patch-types, and had the highest abundance and richness in watersheds with fire and grazing. These results have implications for natural resource management. Riparian fencing of cattle may be a useful practice in areas where water resource protection is the priority. However, overland flow may alter water quality in watersheds with grazers despite fencing. Land managers will need to define management objectives and accept trade-offs in water quality, amphibian and reptile habitat, and cattle production.
Keywords: Cattle; Bison; Amphibian; Reptile; Grasslands; Biology (0306); Conservation Biology (0408); Ecology (0329)